Capanema e a Estrada do Colono: memórias e representações - Schlindwein, Sharlene Keila (2016)
This dissertation has as a research objective memories related to the Estrada do Colono (Rural Work s Road) in Capanema s population. From the contact with this population it was noticed the existence of the subject Estrada do Colono among the population in various moments, aroused some questions, for an example, why a road closed for thirty years is still subject of discussion in the city? Does the Estrada do Colono still exist? How do the people who never passed through it know it? In order to find answers for these and other questions, this dissertation has as its main objective to analyze the memories and for that we turn to some authors like R. Chartier; M. A. Halbwach; M. Pollak; J. Le Goff. The data collection took place from oral research as well as the document research, in newspapers, textbooks and monuments. We propose a qualitative research, because we understand the subject within the complexity of the reality in which it appears, requiring the analysis of this reality as to uncover the memories. Given the complexity of the chosen subject, it is a guided research in interdisciplinarity, so we look for resources in different areas of knowledge, such as geography, sociology, biology, history and others. As a result of this investigation process, we believe that the search for the reopening of the Estrada do Colono, despite being guided by an economist speech, can be understood as a fight for the right to memory. This occurs when we see the redefinition of the Road as a symbol of colonization, and from the perspective of the Road s representation as a tribute to the settlers image, which refers to the pioneers.